PENGARUH LITERASI KEUANGAN, PENDAPATAN DAN TECHNOLOGY ACCEPTANCE MODEL TERHADAP MINAT PENGGUNAAN PAYLATER PADA PEGAWAI LEMIGAS - Hutasoit, Sahala; Naryoto, Pambuko (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of financial literacy, income, and technology acceptance (Technology Acceptance Model/TAM) on the interest in using paylater services. The data used in this study were collected through a survey of 231 individuals who use paylater services. The analytical method employed is multiple linear regression to test the influence of each independent variable on the dependent variable. The results show that financial literacy and TAM have a positive and significant effect on the interest in using paylater, while income has a negative effect on that interest. This study suggests that paylater service providers should focus on improving users' financial literacy and developing accessible technology to enhance user interest. Additionally, companies should pay attention to users in the middle to lower-income segments, who are more likely to be interested in paylater services. This study is expected to contribute to a better understanding of the factors influencing the use of paylater services in Indonesia.